Effects of MATAS Hopscotch technique in the teaching of fractions and error patterns made by Year 5 pupils - Periasamy, Devaki; Abu Bakar, Kamariah; Mohd Ayub, Ahmad Fauzi (Hindawi Publishing Corporation, 2014)
MATAS Hopscotch technique was created to solve the subtraction of three types of fractions. The study involved 56 pupils from two Year 5 classes. A quasi-experimental, nonrandomized control group, pretest-posttest delayed post-test was conducted on two intact groups, randomly assigned into control and experimental groups. A pretest was administered at the early stage of this study. The study described types of error made by the pupils in solving the subtraction of fractions. Rubrics, Hodes and Notling (1998), were used to describe types of error made by the pupils in the pretest and posttest. The findings in the pretest showed both groups made concept, directions, and careless errors. However, in the posttest, the experimental group made careless errors while the control group made concept, directions, and careless errors. The number of errors made by the control group was higher than that made by the experimental group.